Clinical prediction models in hospitalized patients with COVID-19: A multicenter cohort study. (October 2022) - Vedovati, Maria Cristina; Barbieri, Greta; Urbini, Chiara; D'Agostini, Erika; Vanni, Simone; Papalini, Chiara; Pucci, Giacomo; Cimini, Ludovica Anna; Valentino, Alessandro; Ghiadoni, Lorenzo; Becattini, Cecilia
Abstract: Background: Clinical spectrum of novel coronavirus disease (COVID-19) ranges from asymptomatic infection to severe respiratory failure that may result in death. We aimed at validating and potentially improve existing clinical models to predict prognosis in hospitalized patients with acute COVID-19. Methods: Consecutive patients with acute confirmed COVID-19 pneumonia hospitalized at 5 Italian non-intensive care unit centers during the 2020 outbreak were included in the study. Twelve validated prognostic scores for pneumonia and/or sepsis and specific COVID-19 scores were calculated for each study patient and their accuracy was compared in predicting in-hospital death at 30 days and the composite of death and orotracheal intubation. Results: During hospital stay, 302 of 1044 included patients presented critical illness (28.9%), and 226 died (21.6%). Nine out of 34 items included in different prognostic scores were independent predictors of all-cause-death. The discrimination was acceptable for the majority of scores (APACHE II, COVID-GRAM, REMS, CURB-65, NEWS II, ROX-index, 4C, SOFA) to predict in-hospital death at 30 days and poor for the rest. A high negative predictive value was observed for REMS (100.0%) and 4C (98.7%) scores; the positive predictive value was poor overall, ROX-index having the best value (75.0%). Conclusions: Despite the growing interest in prognostic models, their performance in patients with COVID-19 is modest. The 4C, REMS and ROX-index may have a role to select high and low risk patients at admission. However, simple predictors as age and PaO2/FiO2 ratio can also be useful as standalone predictors to inform decision making. Highlights: Predict prognosis in hospitalized patients with acute COVID-19 needs stratification. 12 prognostic scores were evaluated: the overall performance was modest. Nine out of 34 evaluated items of prognostic scores were predictors of death. Age and PaO2/FiO2 ratio can also be useful as standalone predictors of death.